Sosialisasi Alat Peraga PKN “PAKIN” di SD Negeri 1 Tualang Cut Aceh Tamiang - Fatmawati Fatmawati; Ester Julinda Simarmata (Institut Teknologi dan Bisnis Semarang, 2024)
The background for this service is due to problems that arise in class IV students at SD Negeri 1 Tualang Cut, Kab. Aceh Tamiang, namely some students have difficulty in solving problems regarding Indonesia's diversity, therefore student learning outcomes are low. One of the causes of this is due to the teacher's lack of ability to create interesting teaching aids, so that in the learning process students are less active and enthusiastic following ongoing learning. To overcome students' learning difficulties, PAKIN (Indonesian diversity board) is used so that students can be actively involved in learning. The approach or method used is Participatory Action Research (PAR), which is a research model that seeks something to connect the research process to the process of social change. This method aims to produce relevant knowledge. This activity was carried out at SD Negeri 1 Tualang Cut, Kab. Aceh Tamiang. With the